An Expert Perspective on a New Recombinant Pertussis-Only Vaccine and Its Potential Clinical and Programmatic Advantages in Australia, New Zealand, and Beyond - Peter McIntyre; Anita H. J. van den Biggelaar; Frank Beard; Mary Nowlan; Annette K. Regan; Rodney Pearce; Terry Nolan; Catherine Hughes; Peter Richmond (Vaccines, 2026)
Despite high childhood coverage and booster doses of pertussis vaccination across the life course, pertussis (whooping cough) outbreaks continue to occur, including in Australia and New Zealand. In January 2026, the European Medicines Agency (EMA) granted marketing authorisation to a new pertussis-only booster vaccine (VacPertagenTM): the first time in two decades that a new acellular pertussis vaccine has been approved in the European Union. Anticipating future licensure of the vaccine in Australia and New Zealand, an expert panel was convened to discuss the clinical and programmatic advantages that this new vaccine may offer in the context of current pertussis epidemiology and vaccination strategies inSuch advantages may also be applicable to other high-income countries experiencing ongoing pertussis outbreaks.